262 INCREASED OXIDATIVE STRESS INDICATES GREATER RISK FOR PROGRESSION FROM EARLY TO ADVANCED TYPE 2 DIABETIC NEPHROPATHY. Issue 1 (1st January 2007) - Hegazy, K.; Chuahirun, T.; Hudson, C.; Simoni, J.; Wesson, D. E.
Abstract : Purpose: To identify urine parameters in type 2 diabetes mellitus (DM2) that predict progression of early nephropathy defined as microalbuminuria (mg albumin-to-g creatinine ratio [alb/cr] in a spot am urine of 20 to 200 mg/g) to advanced nephropathy defined as macroalbuminuria (urine alb/cr > 200 mg/g). We hypothesized that urine indices of increased oxidative stress predict progression of early to advanced DM2 nephropathy. Methods: We recruited 91 DM2 (39 nonsmokers and 52 smokers) with microalbuminuria and estimated GFR (eGFR) > 90 mL/min. Smokers underwent 12 weeks of smoking cessation intervention and 11 of the 52 (21%) quit. Therefore, three groups were compared: nonsmokers (NS, n = 39), smokers who continued smoking (S, n = 41), and smokers who quit (Quit, n = 11). Subjects were prescribed ACE inhibitors and followed 5 years with yearly measurements of urine alb/cr, eGFR, and oxidative stress as urine excretion of 8-iso-PGF2 alpha (8-iso). Summary: At 5 years, urine alb/cr was higher in S (99.2 ± 13.3) than NS (21.2 ± 1.8) and Quit (23.9 ± 2.3), p < .001). At 5 years, 7 of the 41 S subjects but no NS or Quit subjects had macroalbuminuria. Baseline urine 8-iso excretion was greater in S (4.3 ± 0.5 μg/g cr) and Quit (3.8 ± 0.5 μg/g cr) than NS (1.9 ± 0.3 μg/g cr, p < .02, vs S and Quit). Smoking cessation decreased urine 8-iso excretion in Quit ( 3.8 ± 0.5 to 2.0 ± 0.3 μg/g cr, p < .001) but not in S (4.3 ± 0.5 to 4.0 ± 0.5, p = .71). Initial urine 8-iso excretion was greater in 7 of 41 S subjects who developed macroalbuminuria than in the remaining 34 (6.7 ± 0.8 vs 3.6 ± 0.4 μg/g cr, p < .003). These 34 S subjects did not develop macroalbuminuria but nevertheless had higher initial urine 8-iso excretion and higher 5-year urine alb/cr than NS ( p < .001) and Quit ( p < .03) subjects. Five-year eGFR was not different among groups. Conclusions: The data show that smoking in DM2 is associated with increased oxidative stress as measured by urine 8-iso excretion and that smoking cessation is associated with a reduction in this parameter. Higher levels of urine 8-iso excretion and presumably oxidative stress are associated with progression of DM2 nephropathy.